Pengaruh Locus Of Control Terhadap Kemampuan Eksplorasi Matematis Siswa - Hafizah; Assidiqy, Hasby; Gadih Ranti, Mayang (Lattice Journal : Journal of Mathematics Education and Applied, 2024)
Mathematical exploration ability is an important ability to have nowadays. Various factors are thought to influence a person's mathematical exploration ability, both from a cognitive and affective aspects. One of the affective aspects that affect one's learning achievement is locus of control. This study aims to investigate whether there is an influence of locus of control on mathematical exploration ability of grade XI students of MAN 4 Banjar. The research method used is correlational research. Population of this research is all students of class XI MAN 4 Banjar which amounted to 102 students, while the research sample is one of class XI which amounted to 34 students. The data collection techniques used were tests and questionnaires using mathematical exploration ability test instrument and locus of control questionnaire. The statistical test used is simple regression analysis. The results showed that the locus of control of the XI grade students of MAN 4 Banjar was in the moderate category. Likewise, the mathematical exploration ability of students is in the medium category as well. Simple regression analysis  test results show that there is an effect of locus of control on the students' mathematical exploration ability.   Kemampuan eksplorasi matematis merupakan kemampuan yang penting untuk dimiliki saat ini. Berbagai faktor diduga mempengaruhi kemampuan eksplorasi matematis seseorang, baik dari segi kognitif dan afektif. Salah satu aspek afektif yang mempengaruhi prestasi belajar seseorang adalah locus of control. Penelitian ini bertujuan untuk meneliti apakah ada pengaruh locus of control terhadap kemampuan eksplorasi matematis siswa kelas XI MAN 4 Banjar. Metode penelitian yang digunakan adalah penelitian korelasional. Populasi penelitian ini adalah seluruh siswa kelas XI MAN 4 Banjar yang berjumlah 102 siswa, sedangkan sampel penelitiannya adalah salah satu kelas XI yang berjumlah 34 siswa. Teknik pengumpulan data yang digunakan adalah tes dan angket menggunakan instrumen tes kemampuan eksplorasi matematis dan angket locus of control. Uji statistik yang digunakan adalah analisis regresi sederhana. Hasil penelitian menunjukkan locus of control siswa kelas XI MAN 4 Banjar berada pada kategori sedang. Begitu juga dengan kemampuan eksplorasi matematis siswa berada pada kategori sedang pula. Hasil uji regresi linier menunjukkan ada pengaruh locus of control terhadap kemampuan eksplorasi matematis siswa